2019
DOI: 10.1080/17458080.2019.1614168
|View full text |Cite
|
Sign up to set email alerts
|

Identification of surfactants aggregates on graphitic surface of carbon nanotubes

Abstract: There are a relatively large number of studies on surfactants facilitates the dispersion of multi-walled carbon nanotubes (MWCNTs), however reports for both orientation and size aggregation of surfactants on MWCNTs are scarcely described. In this study, we demonstrate the visualization of the surfactants aggregates onto MWCNTs using atomic force microscopic (AFM) and field emission electron scanning microscopy (FESEM) to provide information on the orientation and the grains size of surfactants-MWCNTs aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…It is expected that a conformation similar to that observed in micelles also exists in the presence of CNPs, ,, whereby the hydrophobic fatty acid chain interacts with the CNP surface, while hydrophilic sorbitan and PEO moieties extend into the aqueous phase. Such a conformation has also been demonstrated by MD simulations and supported by atomic force microscopy . Furthermore, FTIR analysis also revealed a similar mechanism of interaction in the preceding section.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…It is expected that a conformation similar to that observed in micelles also exists in the presence of CNPs, ,, whereby the hydrophobic fatty acid chain interacts with the CNP surface, while hydrophilic sorbitan and PEO moieties extend into the aqueous phase. Such a conformation has also been demonstrated by MD simulations and supported by atomic force microscopy . Furthermore, FTIR analysis also revealed a similar mechanism of interaction in the preceding section.…”
Section: Resultssupporting
confidence: 76%
“…Microscopic examination of multi-walled CNTs (MWCNTs) revealed complete and uniform coverage of the CNT surface with Tween-80 molecules. 17 Field emission electron microscopy analysis revealed a uniform surface coverage of MWCNTs by Tween-80, while atomic force microscopy revealed that Tween-80 aggregates on the MWCNT surface appeared as grains, which were at least 251 nm broad and approximately 6 nm high. Based on the microscopy analysis, the authors proposed that the surfactant Tween-80 molecules appeared to interact with the MWCNT structure through the lipid tail, while the hydrophilic head appears to remain in the aqueous environment.…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The length and density of s-SWCNTs before and after the electrical field alignment were determined through FE-SEM. For this purpose, FE-SEM micrographs were analyzed using the Java-based image processing program known as Image J software …”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, FE-SEM micrographs were analyzed using the Java-based image processing program known as Image J software. 65 4.4. Alignment of s-SWCNTs.…”
Section: Methodsmentioning
confidence: 99%